Saccharomyces cerevisiae boulardii accelerates intestinal microbiota maturation and is correlated with increased secretory IgA production in neonatal dairy calves - Rostoll Cangiano, Lautaro; Villot, Clothilde; Amorin-Hegedus, Rocio; Malmuthuge, Nilusha; Gruninger, Robert; Guan, Le Luo; Steele, Michael (Frontiers in Microbiology, 2023)
Neonatal calves have a limited capacity to initiate immune responses due to a relatively immature adaptive immune system, which renders them susceptible to many on-farm diseases. At birth, the mucosal surfaces of the intestine are rapidly colonized by microbes in a process that promotes mucosal immunity and primes the development of the adaptive immune system. In a companion study, our group demonstrated that supplementation of a live yeast probiotic, Saccharomyces cerevisiae boulardii (SCB) CNCM I-1079, to calves from birth to one week of age stimulates secretory IgA (sIgA) production in the intestine. The objective of the study was to evaluate how SCB supplementation impacts the intestinal microbiota of one-week-old male calves, and how changes in the bacterial community in the intestine relate to the increase in secretory IgA. A total of 20 calves were randomly allocated to one of two treatments at birth: Control (CON, n =10) fed at 5 g/d of carrier with no live yeast; and SCB (n =10) fed at 5 g of live SCB per day (10 × 109 CFU/d). Our study revealed that supplementing calves with SCB from birth to one week of age had its most marked effects in the ileum, increasing species richness and phylogenetic diversity in addition to expediting the transition to a more interconnected bacterial community. Furthermore, LEfSe analysis revealed that there were several differentially abundant taxa between treatments and that SCB increased the relative abundance the family Eubacteriaceae, Corynebacteriaceae, Eggerthellaceae, Bacillaceae, and Ruminococcaceae. Furthermore, network analysis suggests that SCB promoted a more stable bacterial community and appears to reduce colonization with Shigella. Lastly, we observed that the probiotic-driven increase in microbial diversity was highly correlated with the enhanced secretory IgA capacity of the ileum, suggesting that the calf’s gut mucosal immune system relies on the development of a stable and highly diverse microbial community to provide the necessary cues to train and promote its proper function. In summary, this data shows that supplementation of SCB promoted establishment of a diverse and interconnected microbiota, prevented colonization of Escherichia Shigella and indicates a possible role in stimulating humoral mucosal immunity.